Analisis Bahaya Kecelakaan Kerja Proses Produksi Mebel dengan Metode Job Safety Analysis - Alfa Baetin Nurul Ilmy; Tuntas Bagyono; Yamtana Yamtana; Sri Haryanti (Poltekkes Kemenkes Yogyakarta, 2020)
One technique that can be applied to reduce or to avoid occupational accidents is job safetyanalysis (JSA) method, which is determined based on parameters or stages where the accidentsare frequently occur. The purpose of this study is to minimize the danger of workplaceaccidents in the furniture production of PT X by implementing JSA method. The study was anobservational descriptive study. The respondents/sample was 119 out of 169 workers who areselected by using random sampling technique. The data showed that machine II had the greatestpotential for work accidents. These conditions were obtained from the data in previous year,interviews and direct field assessments. The danger posed by occupational accidents can resultin serious or minor injuries to workers' limbs. The OHS section of the company has carried outPPE control, installing OHS signs and initial training. However, work accidents still occur in 2018and 2019. The results of the study indicate that the potential for work accidents can be minimizedby increasing the OHS work program in the company including: improving the quality ofPPE, improving OHS discipline, and finally the application of the method of substitution on a toolthat could potentially cause danger. Thus, the potential hazards and risks can be prevented andmanaged properly. To conclude, JSA method is able to reduce work accidents by a percentagein accordance with the type of work in the production process.